Hodgkin Lymphoma in HIV Positive Patients - Mounier, Nicolas; Spina, Michele; Spano, Jean P. (Current HIV Research, 2010)
Hodgkin Lymphoma (HL) represents one of the most common types of a non-AIDS-defining tumour that occurs in the HIV population, and its incidence is increasing in the post Highly Active Anti-retroviral Therapy (HAART) era. Despite the aggressiveness of that disease, the outcome of patients with HIV-HL has improved with better, combined antineoplastic and antiretroviral approaches. New and effective antiretroviral drugs, in conjunction with nucleoside analogs, improve the control of the underlying HIV infection when used during treatment of HL with chemotherapy. The inclusion of hematopoietic growth factors in the treatment of patients with HIV-HL may allow for the administration of higher dose-intensity chemotherapy and the prolonged use of antiretroviral drugs, with the aim of improving the survival. In addition, new functional imaging tools, like the Positron Emission Tomography (PET), may help to guide treatment and minimize long term toxicity.
Keywords: non-AIDS-defining tumour